PTH-172 Expression patterns of human epidermal growth factor receptor proteins in early gastric cancer. (22nd June 2015) - Arez, M; Butt, MA; Gandy, M; Sehgal, V; Puccio, I; Hamoudi, R; Haidry, R; Novelli, M; Banks, M; Lovat, L; Rodriguez-Justo, M
Abstract : Introduction: Stomach cancer is the 3rd commonest cause of death by cancer worldwide. As many as 60% of these gastric tumours express the Human Epidermal Growth Factor receptor (HER 1–4), which play a role in cell proliferation and survival. Endoscopic submucosal dissection (ESD) is a minimally invasive surgical technique used to resect early gastric neoplasias. The purpose of this study was to establish a relationship between HER family expression in early gastric cancers, their clinical utility as a diagnostic or prognostic adjunct and how over-expression of the HER receptor affects the curative rate of ESD. Method: Formalin fixed paraffin embedded tissue from 22 early gastric ESD resection specimens were sectioned. Normal gastric resections were used as a control. Immunohistochemical staining for the HER family receptors were optimised and staining performed against EGFR external (ED) and internal domain (ID), HER2 (ED and ID), HER3 (ID) and HER4 (ID). Scoring was performed by two independent observers and confirmed by diagnostic software. Results: 2/22 (9%), 2/22 (9%) and 3/22 (13%) of cases were positive for EGFR ID, HER2 ID and HER2 ED respectively. 1/22 (4.5%) of cases showed co-expression of EGFR ID, HER2 ID and HER2 ED. 1 showed HER2 ED and ID co-expression. EGFR ED, HER3 and HER4 were all negative for overexpression. Over-expression of HER2 ID (p = 0.047) and HER2 ED (p = 0.0045) correlated positively with cancer aggressiveness. 10/20 (50%) cases showing no over-expression treated with ESD had reoccurrence of dysplasia, compared to 3/3 (100%) in the over-expressed group (p = 0.21). Conclusion: Though small, our study showed a positive relationship between EGFR and HER2 expression, a potential target for therapeutic treatment. HER3 and HER4 expression did not correlate with any other antibody, in contrast to reported relationships. Repeats with different antibody clones would confirm the reliability of these results. The prognostic utility EGFR and HER2 co-expression to predict an aggressive early gastric cancer phenotype warrants further investigation. Although insignificant, the negative correlation between HER over-expression and ESD curative rates should be followed up with a larger cohort. Disclosure of interest: None Declared.